What Distinguishes Summer Extreme Precipitation From Non‐Extreme Precipitation Over the Tibetan Plateau? - Zhiyuan Ding; Yao Ha; Jingliang Huangfu; Zhong Zhong (Geophysical Research Letters)
Abstract This study focuses on the primary synoptic‐scale patterns and precursors of extreme and non‐extreme precipitation over the Tibetan Plateau (TP). Atmospheric circulation anomalies and their precursors associated with regional extreme precipitation events (REPE) demonstrate distinct precursor wave train and heightened intensity than regional non‐extreme precipitation events (non‐REPE). Specifically, REPE over the northwestern TP (NWTP) exhibits a geopotential height anomaly induced by a latitudinal propagating Rossby wave train along 40°N. In contrast, over the southeastern TP (SETP), REPE is characterized by a geopotential height anomaly caused by a northwest‐southeastward propagating Rossby wave train. The ascending motion anomalies of REPE over both NWTP and SETP are primarily attributed to the geostrophic zonal temperature advection, which is significantly stronger during REPE compared to non‐REPE. This finding provides valuable insights for forecasting summer extreme precipitation over TP.